COVID-19, income and gender wage gap: Evidence from the China family panel studies (CFPS) 2014 to 2020 - Dui, Haojian (Frontiers in Public Health, 2022)
COVID-19 has a ubiquitous impact on human society and a significant impact on the labor market. This paper explores the impact of COVID-19 on income and its gender differences based on Generalized Difference-in-Differences using publicly available national micro-tracking survey data (CFPS 2014–2020) for the first time. The main findings are as follows: 1. COVID-19 significantly reduces incomes and affects men more; 2. Telecommuting mitigates income losses and is a significant factor contributing to the smaller impact on women; 3. There is educational heterogeneity in COVID-19 shock, with a significant negative impact on the income of those with lower education and a non-significant impact on those with higher education; 4. Men working in production and transportation, as well as female workers in commerce and services, will suffer the greatest loss of income; 5. For men, the older they are, the more they are affected by COVID-19, while the opposite is true for women; 6. Compared to urban residents, COVID-19 has a greater impact on rural residents. There are some policy implications: 1. the relationship between COVID-19 prevention measures and economic development should be carefully considered. 2. Telecommuting should be promoted during the COVID-19 pandemic. 3. The vulnerable groups should be protected.